THE SKULL AND TOOTH SYSTEM OF ORLOVICHTHYS LIMNATIS, A LATE DEVONIAN DIPNOAN FROM RUSSIA - Krupina N.I.; Reisz R.R.; Scott D. (My University, 2001)
The cranial anatomy of Orlovichthys limnatis, a Famennian, Late Devonian dipnoan from the Orel region of central Russia, is described on the basis of an almost completely preserved skull, a mandible, and numerous elements of the dentition. Orlovichthys is distinguished from other tooth-plated Devonian dipnoans by its relatively narrow skull and its predatory type of tooth-plate morphology on the pterygoid and prearticular. The marginal dentition of Orlovichthys, which extends transversely across the edge of the ossified ethmoid (upper lip) and along the anterior and lateral edges of the dentary, also appears to be organized as tooth plates. The distribution of marginal dentition among Devonian dipnoans and their probable organization as tooth plates prompts us to suggest that an important developmental constraint may have been associated with the dipnoan dentition throughout the long history of this group.
Keywords: Devonian; Paleozoic::Devonian; Палеозой::Девонская